DEVELOPMENT OF TEACHING MATERIALS BASED ON OUTCOMES BASED EDUCATION CURRICULUM TO IMPROVE TEACHING SKILLS - Sri Dinawaty Suyitno; Abdul Haris Abdullah; Abdurrahman R. Mala (Tadbir: Jurnal Manajemen Pendidikan Islam, 2023)
This research is motivated by the limited availability of teaching materials that are in line with the Outcome-Based Education (OBE) curriculum in the Indonesian Language and Literature Learning Development course at Madrasah Ibtidaiyah. The OBE curriculum emphasizes measurable learning outcomes, strengthening competencies, and adapting to the challenges of 21st century education. The development of OBE-based teaching materials is a strategic step to improve teacher skills, strengthen the relevance of the curriculum, and ensure alignment between objectives, methods, and assessments in the learning process. This research uses a Research and Development (R&D) approach with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The mixed methods approach is used by combining qualitative data through the study of curriculum documents, interviews, and observations, as well as quantitative data through the testing of the effectiveness of teaching materials. The research subjects consist of lecturers and students of the Madrasah Ibtidaiyah Teacher Education Study Program (PGMI) IAIN Gorontalo. The research instruments include expert validation sheets, user response questionnaires, and learning outcome tests. Data analysis was carried out using the percentage of eligibility and N-Gain calculation to assess the improvement in student learning outcomes after the use of teaching materials. The results of the study show that the OBE-based teaching materials developed meet the criteria of valid, practical, and effective. Expert validation scores exceed 80%, signifying good content and presentation feasibility. More than 80% of respondents, both lecturers and students, gave positive responses to the ease of use and relevance of the material. The results of the N-Gain test showed a significant improvement in student learning outcomes after the application of teaching materials. These findings prove that the systematic development of teaching materials with the ADDIE model can increase learning effectiveness and the achievement of student competencies. This study confirms that the application of OBE-based teaching materials contributes to increasing the professionalism of prospective teachers and strengthening the quality of the curriculum in the Islamic higher education environment. The implementation of a curriculum based on learning outcomes not only increases the relevance of learning, but also encourages the creation of teaching innovations that are oriented towards competency achievement. Thus, the results of this research can be used as a model for the development of similar curriculum and teaching materials in other study programs, as well as the basis for improving the quality of higher education that is adaptive, competitive, and results-oriented